Collection and identification of samples contaminated with chemical warfare agents and their degradation products with the use of military equipment for detectingchemical contamination at the site of their occurrence - Monika Kuligowska; Sławomir Neffe (Biuletyn Wojskowej Akademii Technicznej, 2022)
Chemical warfare agents are still a real threat in the surrounding world. They canbe used in armed conflicts and as an alternative to conventional weapons for terrorist groups. The greatchallenge of today’s world is ammunition and barrels filled with deadly poisonous chemicals that aresunk or buried in many regions. The effects of time and environmental conditions have caused thesesubstances to increasingly leak into the areas used by humans, contaminating groundwater, soil, andaquatic organisms. Consequently, drinking water and food products of plant and animal origin arecontaminated. In the face of a threat, an essential element in protecting life and health is the fast detectionof contamination and its reliable identification. This paper gives an overview of the threats caused bychemical warfare agents and residues from the processes of their environmental degradation. It alsoallows us to get acquainted with the latest achievements in detecting and identifying contaminationwhen we know the equipment intended for the needs of the armed forces and stationary chemicallaboratories. The knowledge presented here and the selected data will enable our selection of appropriateequipment for the assigned tasks for members of contamination reconnaissance teams. The proceduresfor handling samples potentially containing chemical warfare agents or their degradation products areessential knowledge for members of military sampling teams. They can also support specialist staffemployed in field and stationary laboratories. The information gathered here will improve the safetyof working with samples contaminated with toxic substances at every stage. Increasing awareness ofthe scale of the threat as well as proper actions and a quick response to the existing contamination dueto the use of the latest technologies will enable us to make well-considered decisions and significantlyimprove the population’s safety.Keywords: chemical sciences, chemical weapons, detection and analysis of chemical warfare agents,CBRN